2017
DOI: 10.1007/s11440-017-0596-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale origin of the thermo-mechanical behavior of clays

Abstract: We investigate the physics behind the complex thermo-mechanical behavior of clays. Depending on their loading history, clays exhibit thermal expansion or contraction, reversible or irreversible, and of much larger magnitude than for usual solids. This anomalous behavior is often attributed to water adsorption, but a proper link between adsorption and thermo-mechanics is still needed, which is the object of this paper. We propose a conceptual model starting from the scale of the adsorption up to the scale of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…• The temperature slightly reduces the range of confining pressures associated with metastability within a clay particle, as observed previously in a basic model of layered adsorbing materials. 6 The energy barriers to be overcome in phase transitions decrease linearly with the temperature at a rate on the order of magnitude of 0.01 kT /nm 2 /K for both 0W/1W and 1W/2W transitions. A kinetic asymmetric behavior is noticed with respect to compressive loading and unloading.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…• The temperature slightly reduces the range of confining pressures associated with metastability within a clay particle, as observed previously in a basic model of layered adsorbing materials. 6 The energy barriers to be overcome in phase transitions decrease linearly with the temperature at a rate on the order of magnitude of 0.01 kT /nm 2 /K for both 0W/1W and 1W/2W transitions. A kinetic asymmetric behavior is noticed with respect to compressive loading and unloading.…”
Section: Discussionmentioning
confidence: 97%
“…For all temperatures, the pressure isotherms seem to fluctuate around water pressure P w after d > 20 Å. A previous study of the authors 6 showed that, with Lennard-Jones fluids confined between 9-3 Lennard-Jones walls, the amplitudes of oscillations globaly decrease with the temperature and this effects is more pronounced for larger basal spacings 6. Here, the amplitudes of 2W states clearly decrease with the temperature, whereas the amplitudes of 1W states at different temeprature are quite…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Strain is calculated by digital image correlation analysis both for total length reduction in the specimen i.e. global strain (1)(2)(3)(4), as well as for a small reference area around the X-ray illuminated area, i.e. local strain the expandable mineral during the relaxation and unloading stages.…”
Section: Monotonic Compression Testmentioning
confidence: 99%
“…More realistic models for the clay response have subsequently been formulated, though they still are mainly based on experimental observations of clay suspensions [6]. The latest generation of models approaches the complete physico-chemical response between the clay minerals and the surrounding water using Molecular Dynamics (MD) simulations, most notably Ebrahimi et al [12] and Brochard et al [4]. These advanced methods, whilst very promising, still would benefit from more experimental evidence on the modelled length scale (nm-lm).…”
Section: Introductionmentioning
confidence: 99%